2022
DOI: 10.3390/world3040048
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Position in Modern Contraceptive Uptake and Fertility Rate among Women of Childbearing Age in 37 Sub-Saharan Countries

Abstract: Women’s socioeconomic position has a significant effect on health services use. With the nature of the socioeconomic empowerment process in relation to improvements in sexual and reproductive health, population-based contraceptive use is key to determining the growth in the human development index of every country. We looked into the effects of women’s socioeconomic position on modern approaches to birth control in sub-Saharan African (SSA) women of childbearing age. A sample of 496,082 respondents was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
3
1
Order By: Relevance
“…Males who are knowledgeable about contraception are more likely than their counterparts who lack this knowledge to participate in FP decisions. This finding was supported by studies conducted in Tanzania [ 77 ] and Ethiopia [ 66 ]. This might be because knowledge of available contraceptive methods enables individuals to make informed decisions and use contraception to plan, delay, and space the pregnancies of their spouses [ 78 ], which is linked to improved birth outcomes for the mother and the newborns, either directly or indirectly.…”
Section: Discussionsupporting
confidence: 76%
“…Males who are knowledgeable about contraception are more likely than their counterparts who lack this knowledge to participate in FP decisions. This finding was supported by studies conducted in Tanzania [ 77 ] and Ethiopia [ 66 ]. This might be because knowledge of available contraceptive methods enables individuals to make informed decisions and use contraception to plan, delay, and space the pregnancies of their spouses [ 78 ], which is linked to improved birth outcomes for the mother and the newborns, either directly or indirectly.…”
Section: Discussionsupporting
confidence: 76%
“…The reasons for the variation could be differences in sample size, study populations, and the study periods. On the other hand, the prevalence of modern contraceptive use in this study was lower than a previous study reported from Southern SSA(57.0%) [28] and Malawi (75%) [27]. The possible reason for the difference might be variations in study settings and the availability of the contraceptive.…”
Section: Discussioncontrasting
confidence: 86%
“…Evidence of the significant influence of women's marital status, age, education, employment status, wealth index, religion, and residence, as well as their partners' education, on the use of contraceptives in the literature [33][34][35], and their availability in the accessed dataset, informed the inclusion of selected covariates. The other covariates included in the analysis were the number of children ever born and the number of living children based on the documentation of their association with contraceptive use [36,37].…”
Section: Explanatory Variablementioning
confidence: 99%